The effects of herbicide application on the properties of agricultural soil in Algeria - Meliani, Kaddour; Oulbachir , Karima; Zemour , Hafidh; Ardjane, Tedj Eddine Adda (Future Science, 2024)
Phytosanitary products, particularly herbicides, are essential for weed control in agriculture. This study examined the concentration and persistence of Pinoxaden residues in different soil textures. Seventy-two soil samples from two farms in Tiaret, Algeria, were analyzed using liquid chromatography (HPLC) to measure herbicide residues. The analysis used a mobile phase of acetonitrile and methanol (50/50, V/V) with a retention time of 2 minutes. Results indicated significant differences in residue persistence based on soil texture. Clay-loam soils showed higher residue persistence, averaging 6.01 × 10^-4 ± 8.7 × 10^-5 μg/g, while sandy soils had lower persistence, averaging 6.4 × 10^-5 ± 5.9 × 10^-6 μg/g. This underscores the impact of soil characteristics on herbicide behavior and the need for tailored management strategies. Despite herbicides' benefits, their environmental impacts are concerning. Persistent residues can contaminate soil and harm ecosystems. Raising awareness among stakeholders about these risks is essential. The study recommends sustainable alternatives, such as biological control methods, to reduce dependency on chemical herbicides. Biological controls offer eco-friendly solutions, promoting ecosystem balance and reducing agriculture's ecological footprint. Implementing crop rotation and other integrated pest management (IPM) strategies can enhance weed control effectiveness while decreasing reliance on chemical herbicides. These practices mitigate environmental risks and improve soil health and agricultural productivity. In conclusion, while herbicides are indispensable in modern agriculture, responsible use and management are crucial for environmental sustainability and the long-term viability of agricultural systems. By adopting sustainable practices and innovative technologies, it is possible to balance agricultural productivity with environmental protection.